On the fringe of COVID-19: our experience in Joseph Hospitals - Balamurugan, Vasanthi; Joseph, Kurian; Kurian, Rekha; Joseph, Tarun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The coronavirus pandemic is an ongoing pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). There is no evidence that pregnant women are more likely to get seriously ill from coronavirus but pregnant women have been included in the list of people at moderate risk (clinically vulnerable) as a precaution. The aim of the study was to determine the incidence of COVID positive cases and its management. Methods: This is a prospective observational study done in the Department of OBGYN, Joseph hospitals, Chennai, Tamil Nadu over a period of 4 months (April-July 2020). Results: Over the month of April and May, among the tested population none had positive result. But in the month of June and July, we had 6.3% and 8.2% of patients tested positive among the population due to universal screening. Conclusions: This study highlights the difficulty in small hospitals to allocate the resources, handle the patient and importantly protect the staff. These are difficult times and the private hospitals must come forward to help the government set up in handling the cases on “the fringe of COVID”.